Understanding David Foster Wallace : revised and expanded edition - Boswell, Marshall, 1965- (Book collections on Project MUSE., 2020)
"Since its publication in 2003, Understanding David Foster Wallace has served as an accessible introduction to the rich array of themes and formal innovations that have made Wallace's fiction so popular and influential. The original edition addressed only his first four works of fiction-The Broom of the System, Infinite Jest, Girl with Curious Hair, and Brief Interviews with Hideous Men. This revised edition covers his final story collection, Oblivion, and his posthumous novel, The Pale King. Although critics sometimes label Wallace a postmodern writer, Marshall Boswell argues that he should be regarded as the nervous leader of some still-unnamed (and perhaps unnamable) third wave of modernism. Boswell's study directly confronts such arcane issues as postmodernism, information theory, semiotics, the philosophy of Ludwig Wittgenstein, and poststructuralism, yet it does so in a way that is comprehensible to a wide and general readership"--